- Corporate managers' awareness of religious teachings and its impact on corporate social responsibility disclosure - A quantitative study - Darawi, Muamr Ahmed; Ayedh, Abdullah Mohammed (Journal of Economic, Administrative and Legal Sciences, 2020)
The aim of this paper is to determine the impact of awareness of religious teachings on corporate social responsibility disclosure in Libya. To achieve this aim (310) of the questionnaires were distributed to respondents who are the managers of companies operating in Libya in 2018. The spss modeling was used in the descriptive analysis of the data, and the intelligent modeling used the least squares (PLS-SEM) to test the hypothesis study. The study found that there is a positive relationship between the company manager's perception of religious teachings related to the social responsibility disclosure and the corporate social responsibility disclosure level of the companies which operate in Libya. The impact has extended to the four dimensions of disclosure: community disclosure, environmental disclosure, employee disclosure, and product - Customer disclosure.
Keywords: Disclosing social responsibility; Awareness of religious teachings